9(x+6)+2(x+6)=6x-6

Simple and best practice solution for 9(x+6)+2(x+6)=6x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+6)+2(x+6)=6x-6 equation:


Simplifying
9(x + 6) + 2(x + 6) = 6x + -6

Reorder the terms:
9(6 + x) + 2(x + 6) = 6x + -6
(6 * 9 + x * 9) + 2(x + 6) = 6x + -6
(54 + 9x) + 2(x + 6) = 6x + -6

Reorder the terms:
54 + 9x + 2(6 + x) = 6x + -6
54 + 9x + (6 * 2 + x * 2) = 6x + -6
54 + 9x + (12 + 2x) = 6x + -6

Reorder the terms:
54 + 12 + 9x + 2x = 6x + -6

Combine like terms: 54 + 12 = 66
66 + 9x + 2x = 6x + -6

Combine like terms: 9x + 2x = 11x
66 + 11x = 6x + -6

Reorder the terms:
66 + 11x = -6 + 6x

Solving
66 + 11x = -6 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
66 + 11x + -6x = -6 + 6x + -6x

Combine like terms: 11x + -6x = 5x
66 + 5x = -6 + 6x + -6x

Combine like terms: 6x + -6x = 0
66 + 5x = -6 + 0
66 + 5x = -6

Add '-66' to each side of the equation.
66 + -66 + 5x = -6 + -66

Combine like terms: 66 + -66 = 0
0 + 5x = -6 + -66
5x = -6 + -66

Combine like terms: -6 + -66 = -72
5x = -72

Divide each side by '5'.
x = -14.4

Simplifying
x = -14.4

See similar equations:

| 3x-2x=8+x | | 6+5t-6t^2=0 | | -2(3+x)+5x=24 | | 5x-30+2=7x-6 | | 10h/108=5/9 | | 7k+2=3k-1 | | 7+4x-9=-9 | | x-4y-12-5y+8y= | | 6+0.75x=x+3 | | 120+360+x=900 | | 3x+1=58 | | f(-5)=2a+3 | | 4x+1=63 | | 2*(x+9)-6= | | 3r+7=-5 | | 5.6=1.1+1.2 | | 2x+(4x-1)=2(5x+3)+4x | | 4m^2-28m-32=0 | | 3-2x(3)=12x | | 7x-1-4=1 | | 20x-(9x-7)=40 | | 6x^2-16x-20=0 | | 2t-10=4 | | 34+17= | | rx+sx=1 | | 8x-(6x+4)=2 | | -5p+4+6p=13 | | 34=w-17 | | .25r-.25+.25r=.5-.25 | | X^2+12x=14 | | x^3+3x^2-28x=0 | | -15(3p-2)+10(4p+2)=p-(8p-32) |

Equations solver categories